Occurrence of typical antibiotics, representative antibiotic-resistant bacteria, and genes in fresh and stored source-separated human urine. (January 2021) - Zhou, Xiaoqin; Cuasquer, Gabriela Jacqueline Perez; Li, Zifu; Mang, Heinz Peter; Lv, Yaping
Graphical abstract: Highlights: 20 randomly real urine samples were collected and analyzed. Totally 30 antibiotics in the fresh real urine were identified. Representative antibiotic resistance bacteria and its gene were identified. Changes of antibiotics, antibiotic resistance bacteria and gens of urine were monitored. Abstract: Human urine is a source of fertilizer and, with proper management, it can be reused in agriculture. Determining the contamination issue of antibiotics in source-separated urine is important because the majority of antibiotics are excreted with urine. In this study, source-separated urine samples were randomly collected from a male toilet in a university building and analyzed in terms of 30 typical antibiotics (including 14 sulfonamides, 4 tetracyclines, and 12 fluoroquinolones) and tetracycline-resistant Escherichia coli, as well as its antibiotic-resistant genes to determine the contamination characteristics of antibiotic-related pollution in fresh and stored urine. Results showed that 18 out of 30 typical antibiotics were detected in fresh source-separated human urine. The dominant antibiotic was oxytetracycline with a frequency of 100%, followed by tetracycline, sparfloxacin, enrofloxacin, and ofloxacin, which demonstrated a detection frequency of 55%. Among the detected values, sulfonamides (2 antibiotics), tetracyclines (4 antibiotics), and fluoroquinolones (12 antibiotics) had a concentration range of 0.25–2.94, 0.94–41.2, and 0.06–163.16 ng/mL, respectively. Furthermore, tetracycline-resistant Escherichia coli, which was measured using plate count method, and its related gene, tet M, exhibited a maximum cell density of (200, 000 ± 5000) CFU/100 mL and (2.73 ± 0.261) × 10 7 copies/mL, respectively. When the fresh urine was stored in an ambient environment for 30 days to simulate the real circumstances of urine management, a significant reduction in antibiotics and antibiotic-resistant bacteria was observed, while the change in antibiotic-resistant genes was insignificant. The results of this study suggest that risks associated with antibiotics and their antibiotic-resistant bacteria and genes are retained during collection and storage. Hence, these kinds of microcontaminants must be considered in further urine utilization.